Running with Mother - Mlalazi, Christopher (Book collections on Project MUSE., 2012)
Unsentimental and unselfpitying, this short but powerful novel by Chris Mlalazi vivifies an account by Rudo, a fourteen-year-old school girl who observes the terrifying events that take place in her village. Running with Mother provides us with a gripping story of how Rudo, her mother, her aunt and her little cousin survive the onslaught. Shocking as the story that unfolds may be, it is balanced by the resilience, self-respect, unselfishness and stoicism of the protagonists. Mlalazi's novel is written with insight, humour and provides a salutory reminder that even in the worst of times, we can find humanity.